2018
DOI: 10.1088/1748-3190/aaef1d
|View full text |Cite
|
Sign up to set email alerts
|

Training bioinspired sensors to classify flows

Abstract: We consider the inverse problem of classifying flow patterns from local sensory measurements. This problem is inspired by the ability of various aquatic organisms to respond to ambient flow signals, and is relevant for translating these abilities to underwater robotic vehicles. In Colvert, Alsalman and Kanso, B&B (2018), we trained neural networks to classify vortical flows by relying on a single flow sensor that measures a 'time history' of the local vorticity. Here, we systematically investigate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
(76 reference statements)
2
31
0
Order By: Relevance
“…2019), flow field reconstruction and prediction (Maulik & San 2017; Maulik et al. 2018; Fukami, Fukagata & Taira 2019; Huang, Liu & Cai 2019; Lee & You 2019) and, more relevant to the present study, flow field identification (Colvert, Alsalman & Kanso 2018; Alsalman, Colvert & Kanso 2019; Wu et al. 2019 b ).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…2019), flow field reconstruction and prediction (Maulik & San 2017; Maulik et al. 2018; Fukami, Fukagata & Taira 2019; Huang, Liu & Cai 2019; Lee & You 2019) and, more relevant to the present study, flow field identification (Colvert, Alsalman & Kanso 2018; Alsalman, Colvert & Kanso 2019; Wu et al. 2019 b ).…”
Section: Introductionmentioning
confidence: 82%
“…Once the training process is finished, the classifier can be used to classify a given sample automatically. An example of the application of the classification method in fluid mechanics is the classifier of wake pattern in the flow past an airfoil by Colvert et al (2018) and Alsalman et al (2019). They used a neural network to train the classifier for classifying the wake pattern generated by different motions of the airfoil.…”
Section: Introductionmentioning
confidence: 99%
“…6), we find that the novel y component is more informative for discerning between objects. Combining the two measuring dimensions improves classification even further, which also holds for object localization [11], [36].…”
Section: D Sensingmentioning
confidence: 90%
“…More directly, zero crossings, maxima, and minima of the velocity profile can also be directly used to produce estimates for the distance (y-coordinate) and the lateral position (x-coordinate) [10]. In [30], [36], [37], it is shown that an ALL comprising of 2D-sensitive sensors makes localization more robust. Compared to the 1D sensitivity of fish and most other ALL implementations, this extension provides more and complementary spatial reference points [30], [36], which may also be helpful for shape recognition.…”
Section: ) Velocity Profilesmentioning
confidence: 99%
“…More directly, zero crossings, maxima, and minima of the velocity profile also directly produce estimates for the distance (y-coordinate) and the lateral position (x-coordinate) [43]. In [9,77,122], it is shown that an ALL comprising of 2D-sensitive sensors makes localization more robust. This extension compared to the 1D sensitivity of fish and most other ALL implementations, provides more and complementary spatial reference points [9,122], which may also be helpful for shape recognition.…”
Section: Velocity Profilesmentioning
confidence: 99%